Socio-economic and cultural context of Bangladeshi women in North-East England - Khatoon, Pathema Zhura (2006)
My research looks at the different socio-economic and cultural aspects of Bangladeshi ethnic minority women living in North-East England. Given the nature of the topic and constraints due to my personal circumstances, I conducted an efficient social survey which achieved a high response rate without compromising good standards of research. Ethical considerations also influenced the detail of how the research methods were chosen, implemented and interpreted. Participatory observation and an in-depth questionnaire associated with semi-structured interview data were used to produce basic information on the extent and effects of the variables in my research. Focus group meetings were also valuable in revealing the multiple understandings of participants regarding different issues in my research. I also engaged with Visual Ethnography in order to accumulate further, complementary information. The thesis shows the different socio-economic and cultural characteristics of the daily living experience of immigrant Bangladeshi women living in different parts of Northeast England. Different issues like demographic characteristics, including migration status, economic activities, movements, different fears, anxieties, wariness, housing and health conditions, were surveyed. The research shows that Bangladeshi women are constrained by many social, cultural and practical difficulties, including conservative attitudes to the role of women in their own community. The language barrier is also problematic for many women, along with a lack of educational qualifications. Further research is now required on the lifeworlds of Bangladeshi women in Britain and the various factors in their lack of empowerment